Permohonan Dispensasi Nikah Tanpa Orang Tua atau Wali - Ulin Nikmatul Badriyah (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Marriage can not be implemented if the brides or one of the bride has not reached the age limit that has been determined, which is 19 years for men dan16 years for women. This statement specified in Law No. 1 Year 1974 on Marriage Article 7 paragraph (1). If a man or woman who try to carry out the marriage before that age she must obtain a permission in the form of dispensation of marriage proposed by both parents or guardian of the man or woman to the courts in the area. But the establishment of the Religious Court Panel in Kediri on the application for dispensation of marriage in the case Number: 0024 / Pdt.P / 2014 / PA.Kdr, marriage dispensation petition should be filed by the bride. This study aims to determine the legal considerations of Religious Court in Kediri in defining marriage dispensation which the petition is filed by the bride him/herself, without the presence of parents or guardians in the trial, as well as reviewing the legality of the applicant of such determination. As in this study, the authors used a qualitative approach and field research, while the method of data collection is interview and documentation. The data analysis process was done through data reduction, data presentation, and conclusion. The results of this study concluded that there are seven consideration of the judge in granting the request for dispensation of marriage without a parent or guardian, namely: 1) The procedural law which applied in the Religious Court of Kediri, 2) The reason for the filing of dispensation of marriage is because the bride is pregnant before the marriage, 3 ) there is no prohibition to marry the bride, 4) the readiness of the bride, 5) There is goodness for the brides, 6) The is an obstacle for the parents to be present during the trial, 7) Maturity of the applicant. As the legality of the applicant of such determination is legitimate, it means that the assignment is not null and void because it already contains a series of proceedings in the trial and it is not considered as reducing the parts of the proceedings. Based on the terms of the substance of the determination, it has a formal function and can be implemented, meaning that copies of such determination can be used as a requirement for marriage in the Office of Religious Court. Such designations have a power from the applicants, in this case the Court of Kediri establishes a state where the applicant can marry to the partner, although age is still under the provisions of Marriage Law No. 1 of 1974.